PIG PRODUCTION SYSTEM IN THE STATE OF ANDHRA PRADESH AND CONSTRAINTS FACED BY FARMERS- A SURVEY REPORT - Ashalatha, P; Prbhakar, K (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A study was conducted to analyze the current pig production system in the state of Andhra Pradesh and various constraints faced by farmers of the state towards adoption of scientific technologies of pig rearing. A total of 400 farmers were covered from 4 districts of the state and 10 villages in each district. The major constraints perceived by the farmers were inadequate knowledge of scientific feeding (87.00 %) housing (65.45%), breeding and health cover measures. In breeding aspect, the major shortfall was non availability of upgraded variety of pigs (78.13%) which are good in production potential in the local market of the remote villages. There was lack of knowledge of identifying infection and contagious diseases (93.25%), advantages of proper cleaning of pig shed (73.69%), non-availability of timely veterinary facilities (66.33%), poor economic condition (76.00%) of the farmers was also a major constraint for adopting scientific technologies regarding pig rearing. Considering these facts it is necessary to formulate suitable strategy for various extension activities in rural remote areas of the state to ameliorate the constraints perceived by the farmers.